(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
VANETs place an important role in an intelligent transportation system. The main aim is to exchange traffic information to avoid accidents and provide proper communication between the vehicles. A great challenge for VANETs is managing of high mobility and fast changes in the topology. VANETs suffer from the problem of undesired signals. Various mechanisms have been proposed for undesirable signals. But all these methods are having problems like high signaling, slow convergence rate, and computational complexity, etc., This technique is proposed for 5G VANETs using fusion Beam forming Algorithms and this is an optimum technique between simple and complex techniques. We have designed and implemented the novel method using MATLAB simulation and outcomes show that our method gives more accurate values of the location of mobile vehicles, and precise cancellation of interference signals compared to other existing methods, and we have tested the implemented simulation program with some known speech signals.